Plant Growth-Promoting Bacteria (PGPB) for Sustainable Agriculture: Current Prospective and Future Challenges - Esha Kumari; Sneha Kumari; Sai Santosh Das; Manaswini Mahapatra; Jyoti Prakash Sahoo (AgroEnvironmental Sustainability)
Sustainable agriculture is a global imperative to meet the challenges of food security and environmental protection. Plant Growth-Promoting Bacteria (PGPB) have emerged as key players in sustainable agricultural practices due to their diverse roles in enhancing plant growth, nutrient uptake, stress tolerance, and disease resistance. This review explores the diverse facts about PGPB and their potential applications in sustainable agriculture. The review begins by elucidating the mechanisms underlying PGPB-plant interactions, including phytohormone production, nutrient solubilization, and biocontrol activities. This review delves into the intricate signalling networks involved in PGPB-induced systemic resistance. In addition, this review discusses the pivotal role of PGPBs in mitigating abiotic stresses such as drought, salinity, and heavy metal toxicity, highlighting their contributions to climate-resilient agriculture. The ecological implications of PGPB application in sustainable agriculture are discussed, emphasizing the need for responsible and environmentally friendly practices. Furthermore, the use of PGPB for sustainable agriculture holds great promise for addressing the challenges of food security and environmental sustainability. In addition, this review provides a comprehensive overview of the multiple roles, mechanisms of action, and potential applications of PGPB, while emphasizing the importance of responsible and environmentally sound approaches in realizing the full potential of PGPB for a resilient and sustainable agricultural future.